Transcutaneous Vagus Nerve Stimulation Regulates the Cholinergic Anti-inflammatory Pathway to Counteract 1, 2-Dimethylhydrazine Induced Colon Carcinogenesis in Albino wistar Rats - Rawat, Jitendra K.; Roy, Subhadeep; Singh, Manjari; Guatam, Swetlana; Yadav, Rajnish K.; Ansari, Mohd Nazam; Aldossary, Sara A.; Saeedan, Abdulaziz S.; Kaithwas, Gaurav (Frontiers in Pharmacology, 2019)
The present study was undertaken to study the effects of transcutaneous auricular vagus nerve stimulation (taVNS) on 1, 2-dimethyhydrazine (DMH) induced colon cancer and role of the cholinergic anti-inflammatory pathways (CAP) in the same. Group of rats were randomly divided into ten groups (n=8). DMH administration was very well apparent for autonomic dysfunction as observed through distorted hemodynamic [electrocardiogram (ECG) and heart rate variability (HRV)], increased aberrant crypt foci (ACF) and flat neoplastic lesions [methylene blue staining, scanning electron microscopy (SEM) and Hematoxylin and eosin staining (H&E staining)]. DMH administration was also recorded for per-oxidative damage. taVNS application restored the autonomic function, cellular morphology and curtailed the oxidative damage. DMH application conspicuously inhibited the mitochondrial apoptosis which was restored back after taVNS application, when scrutinized through immunoblotting and quantitative real time polymerase chain reaction (qRT-PCR) studies. taVNS application up-regulated the CAP as perceived through increased expression for α7 nicotinic acetylcholine receptor(α7nAchR) and decreased expression for nuclear factor kappa-ligand-chain-enhancer of activated B cells (NFκBp65), tissue necrosis factor- α (TNF-α) and high mobility group box-1 (HMGB-1) at protein and mRNA levels. All in all, taVNS up-surged the CAP to counteract DMH induced colon carcinogenesis. Among all the stimulation parameters used, taVNS 3 (pulse width-1 ms, frequency-6Hz, voltage-6v, duration- 240 min.) was observed to be most effective. Since chemotherapy and surgery are available options for management of CRC, which are troublesome and painful. There is no non-invasive method available for management for CRC till date. Results of the current study affirmed, effectiveness of taVNS against DMH induced colon cancer. Present study established taVNS as novel and non-invasive approach towards the management of CRC.